Alterations in the Gut Microbiome of Young Children with Airway Allergic Disease Revealed by Next-Generation Sequencing - Wan J; Song J; Lv Q; Zhang H; Xiang Q; Dai H; Zheng H; Lin X; Zhang W (Journal of Asthma and Allergy, 2023)
Jinyi Wan,1,2,* Jingjing Song,1,* Qingqing Lv,2 Hui Zhang,1 Qiangwei Xiang,1 Huan Dai,1 Hang Zheng,1 Xixi Lin,3 Weixi Zhang1 1Department of Pediatric Allergy and Immunology, The Second Affiliated Hospital and Yuying Children’s Hospital of Wenzhou Medical University, Wenzhou, 325027, People’s Republic of China; 2Department of Pediatric Internal Medicine, Taizhou Hospital of Zhejiang Province affiliated to Wenzhou Medical University, Taizhou, 317000, People’s Republic of China; 3Department of Pharmacy, The Second Affiliated Hospital and Yuying Children’s Hospital of Wenzhou Medical University, Wenzhou, 325027, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xixi Lin; Weixi Zhang, Email lxx592604326@163.com; zhangweixi112@163.comPurpose: Recent studies had shown that gut microbiota played a significant role in the development of the immune system and may affect the course of airway allergic disease. We conducted this study to determine unique gut microbial associated with allergic disease in children by shotgun gene sequencing.Methods: We collected fecal samples from children with allergic asthma (n = 23) and allergic rhinitis (n = 18), and healthy control (n = 19). The gut microbiota of specimens was analyzed by high-throughput metagenomic shotgun gene sequencing.Results: The intestinal microbiota of children with allergic asthma and allergic rhinitis was characterized by increased microbial richness and diversity. Simpson and Shannon were significantly elevated in children with allergic asthma. Principal coordinates analysis (PCoA) showed that the gut microbial communities cluster patterns of children with asthma or rhinitis were significantly different from those of healthy controls. However, no significant difference was found between asthma group and rhinitis group At the phylum level, higher relative abundance of Firmicutes was found in the allergic rhinitis group and allergic asthma group, while the level of Bacteroidetes was significantly lower. At the genus level, Corynebacterium, Streptococcus, Dorea, Actinomyces, Bifidobacterium, Blautia, and Rothia were significantly enriched in the allergic asthma group. Finally, a random forest classifier model selected 16 general signatures to discriminate the allergic asthma group from the healthy control group.Conclusion: In conclusion, children in the allergic rhinitis group and allergic asthma group had altered gut microbiomes in comparison with the healthy control group. Compared to healthy children, the gut microbiome in children with allergic diseases has higher pro-inflammatory potential and increased production of pro-inflammatory molecules.Keywords: childhood, allergic asthma, allergic rhinitis, gut microbiome, metagenomic sequencing